Application Of Android-Based Scms Applications In The Establishment Of Student Character Primary School - Sukaryo, Sukaryo (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to examine the effectiveness of the application of an Android-based SCMSapplication in the formation of the character of elementary school students, to describe thecharacter of students in elementary schools, to measure the effectiveness of the applicationof an Android-based SCMS application in the formation of the character of elementary schoolstudents. This research is a type of quantitative research with the subject of elementaryschool students in Wonosobo district, as well as with the object of students in SDMuhammadiyah Sudagaran Wonosobo. Data collection tools in the form of questionnaires,observations and interviews. The data analysis technique used in this research is descriptiveanalysis and correlation analysis. The main findings of the study show that the results of thecorrelation product moment calculation obtained rcount of 0.938 and rtable = 0.514 at asignificance level of 5%, meaning that rcount > rtable, then there is a significant influenceon the application of the Android-based SCMS application in character building ofelementary school students, with a known determination test. that contributes 88% ininfluencing the character of students.